The Effect of the Liveworksheet Media-Assisted Problem-Based-Learning Model on the Ability to Write Explanatory Texts of Grade IX Students at UPT SMP Negeri 8 Medan - Febina Maharani Br Tarigan; Lili Tansliova (Journal of English Language and Education, 2026)
This study aims to determine the effect of the Problem Based Learning model assisted by Liveworksheet media on students' ability to write explanatory texts. This study uses a quantitative approach with an experimental method. The research design used is a Two Group pretest-posttest group design. Data collection techniques through tests, interviews, and observations. The results of the study from the application of the Problem Based Learning model assisted by Liveworksheet media show that: 1) Before being given treatment, the ability to write explanatory texts in both groups was in the low category with an average pre-test of the experimental group of 55.67 and the control group of 57.50. 2) After being given treatment, the experimental group experienced a significant increase to the good-very good category with an average post-test reaching 81.17, far exceeding the average post-test of the control class which only reached 66.67. 3) Based on the hypothesis test (Independent Sample T-test), a significance value of 0.001 was obtained, and the N-Gain Score test results indicated an effectiveness level of 58.18% for the experimental class (fairly effective), while the control class was only 20.76% (ineffective). Based on the research results, it can be concluded that the implementation of the Problem-Based Learning model assisted by Liveworksheet media has a significant impact on the writing ability of ninth-grade students at the UPT SMP Negeri 8 Medan.